Increased body fat rather than body weight has harmful effects on 4-year changes of renal function in the general elderly population with a normal or mildly impaired renal function - Kim JK (Dove Medical Press, 2014)
Jwa-Kyung Kim,1 Young Rim Song,1 Young-Jun Kwon,2 Hyung Jik Kim,1 Sung Gyun Kim,1 Young-Su Ju21Department of Internal Medicine, Kidney Research Institute, 2Department of Occupational and Environmental Medicine, Hallym University Sacred Heart Hospital, Anyang-si, South KoreaBackground: With increasing age, body fat increases and muscle mass reduces. Even people with a normal weight may have a higher percentage of body fat. The aim of this study is to investigate the association between increased body fat and renal function decline (RFD) in the general elderly population with normal or mildly impaired renal function.Method: We conducted a prospective study of 615 healthy individuals in the general Korean population aged ≥60 years who participated in two health screening check-ups separated by a 4-year period. Obesity was defined as the highest sex-specific tertiles of the percentage body fat (PBF). The main outcome was changes of estimated glomerular filtration rate (eGFR) during the 4 years. Significant RFD was defined as a decrease of eGFR over the upper quartile (≤-2.1% per year). Results: The mean age was 67.2±6.6 years. The median value of the absolute decline in the eGFR and the percent change was -3.0 mL/minute/1.73 m2 and -0.87%/year in men and -3.1 mL/minute/1.73 m2 and -0.89%/year in women, respectively. When stratified by sex-specific PBF tertiles, pronounced differences were observed in both sexes; those at the highest tertile of PBF showed the greatest decline in eGFR. Even after adjustments for traditional risk factors of RFD, PBF was independently associated with eGFR changes (ß=-0.181; P<0.001). In addition, the harmful effect of a high PBF was consistently found in subjects with a normal weight, too (ß=-0.141; P=0.006). Cases of significant RFD occurred in 181 participants (29.4%), and the risk was higher in obese participants as compared with the nonobese participants. The odd ratios (95% confidence interval) for significant RFD were 2.76 (1.28–7.74) in men and 2.02 (1.06–4.43) in women in a whole population and 3.15 (1.03–18.52) in men and 1.44 (1.01–3.28) in women with a normal weight, respectively.Conclusion: Among the elderly population without comorbidities, increased body fat has a harmful effect on RFD, irrespective of body weight. Keywords: body fat, general elderly population, renal function decline, obesity